Critical Size Bone Defect Healing Using Collagen–Calcium Phosphate Bone Graft Materials - Walsh, William Robert (PLoS One, 2017)
The need for bone graft materials to fill bony voids or gaps that are not related to the intrinsic stability of the bone that arise due to trauma, tumors or osteolysis remains a clinically relevant and significant issue. The in vivo response of collagen–tricalcium phosphate bone graft substitutes was evaluated in a critical size cancellous defect model in skeletally mature rabbits. While the materials were chemically virtually identical, new bone formation, implant resorption and local in vivo responses were significantly different. Differences in the in vivo response may be due, in part, collagen source and processing which influences resorption profiles. Continued improvements in processing and manufacturing techniques of collagen—tricalcium phosphate bone graft substitutes can result in osteoconductive materials that support healing of critical size bone defects even in challenging pre-clinical models.